Kindrachuk M.V., Mishchuk O.A., Khlevna Yu.L., Danilov A.P. Peculiar state of surface layers of the branch-steel pair contact friction zone. - Кіндрачук, М.В.; Міщук, О.О.; Хлевна, Ю.Л.; Данілов, А.П. (Problems of Tribology, 2014)
By the methods of Auger electron spectroscopy and nanoscopic surface layer ion etching, scanner electron and optical microscopy, the conjugate micro-regions of the friction surfaces of the bronze-steel pair were archived. New data about the creation mechanism and properties of surface “served film” on the bronze were found. The elemental density and surface thin-layer structure of friction contact zone were analyzed. The high dense elemental state of the “served film” in the branch pre-surface layer was evinced.